The function pdsolve gives different answers depending upon the way the problem is posed. For example:
> ans1 := u(x,t) = b/(-x+_F1(-(-t*b+a*x)/b)*b);
which is the same problem but with u(x,t) replaced by u(t,x), gives:
> ans2 := u(t,x) = a/(-t+_F1((-t*b+a*x)/a)*a);
Both are actually correct solutions, as is easily verified by a call to pdetest.
My query is:
1) Why does the Maple solution vary according to how u is specified?
2) is it posible to get Maple to automatically provide both solutions regardless as to how u is specified?
Any help appreciated.